Accessing the Economic Value of Natural Snows in Ski Resort Using Contingent Valuation Method - HEO, Jaewan; NAM, Seungmin (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021DO - 10.14505//jemt.12.3(51).16, 2021)
The purposes of this study are to estimate an individual’s probability of willingness to pay tax for preservation of the snows ski resorts in South Korea by using the CVM; and to present the effects of 4Es of the Experience economy theory in the experience economy theory. Truncated mean WTP indicates that the economic value of the natural snows of ski resort in Korea is 172 won (about 17 U.S cents) per household, which is a preservation value. Hence, in the practical perspective, policy makers are able to determine whether they should consistently develop and invest on the preparing for the climate change in the ski resort or not.